2013
DOI: 10.1161/circulationaha.113.004747
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lower and Upper Gastrointestinal Bleeding, Transfusions, and Hospitalizations With Complex Antithrombotic Therapy in Elderly Patients

Abstract: Background-Complex antithrombotic therapy (CAT) prescribed to elderly patients increases the risk of gastrointestinal bleeding. We quantified upper (UGIE) and lower gastrointestinal (LGIE) events, transfusions, and hospitalizations in a national cohort of elderly veterans prescribed CAT. Methods and Results-Veterans ≥60 years of age prescribed anticoagulant-antiplatelet, aspirin (ASA)-antiplatelet, ASAanticoagulant, or triple therapy (ie, TRIP, anticoagulant-antiplatelet-ASA) were identified from the national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 40 publications
1
56
0
2
Order By: Relevance
“…Yet, PPI use is usually a strong marker of worse overall comorbidity. 11 Nevertheless, new studies should further investigate this effect, because recent experimental animal data suggest that PPI can alter the microbiota of the small bowel and potentiate the damaging effect of NSAIDs on the intestinal mucosa. 20 This study has strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, PPI use is usually a strong marker of worse overall comorbidity. 11 Nevertheless, new studies should further investigate this effect, because recent experimental animal data suggest that PPI can alter the microbiota of the small bowel and potentiate the damaging effect of NSAIDs on the intestinal mucosa. 20 This study has strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…9 Evidence on the risk of lower gastrointestinal bleeding (LGIB) associated with other non-aspirin antiplatelet or anticoagulant agents is related only to diverticular bleeding and is also very scarce, 10 whereas it is clear that use of these drugs is growing in a progressively elderly population. 11 Different studies have shown that the use of proton pump inhibitors (PPIs) prevents upper GI damage and the risk of upper GI complications but is unable to prevent NSAID-associated small bowel mucosal damage. 1,6 No data are available concerning the impact of PPI use on lower GI complications.…”
mentioning
confidence: 99%
“…We found that patients with diverticular bleeding used significantly more PPIs than patients with diverticulitis and the controls, but we did not find that PPIs increased the risk of diverticular bleeding in the multivariate logistic analysis of significant risk factors. PPIs are some of the most commonly prescribed medications and are often a strong indicator of worse overall comorbidities [19]. Nagata et al [20] also demonstrated that PPIs did not lead to an increased risk of lower gastrointestinal bleeding in a large case-control study.…”
Section: Doi: 101159/000491875mentioning
confidence: 99%
“…In addition to reducing cardiovascular risk, however, antiplatelet therapies confer an increased risk of bleeding in general [68] and of upper gastrointestinal bleeding (UGIB) in particular [1012]. The risk of lower gastrointestinal bleeding (LGIB) associated with antiplatelet therapies, however, has rarely been studied and only in small populations [1315] or elderly patients [16]. …”
Section: Introductionmentioning
confidence: 99%